Given that positive integers a , b and c satisfy the equation a 2 + b 2 = c 2 with a , b consecutive, and we know that ( a , b , c ) = ( 3 , 4 , 5 ) , ( 2 0 , 2 1 , 2 9 ) are two smallest possible solutions satisfying this constraint such that c is minimized. What is the third smallest value of c ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By computer science, we get the answer 169 when a=119.
Claim: If a , c are such that a 2 + ( a + 1 ) 2 = c 2 , then the same is true for ( a ′ , c ′ ) = ( 3 a + 2 c + 1 , 4 a + 3 c + 2 ) . Proof: ( a ′ ) 2 + ( a ′ + 1 ) 2 = ( 3 a + 2 c + 1 ) 2 + ( 3 a + 2 c + 2 ) 2 = 1 8 a 2 + 8 c 2 + 2 4 a c + 1 8 a + 1 2 c + 5 ; ( c ′ ) 2 = ( 4 a + 3 c + 2 ) 2 = 1 6 a 2 + 9 c 2 + 2 4 a c + 1 6 a + 1 2 c + 4 . The difference between these two expressions is ( a ′ ) 2 + ( a ′ + 1 ) 2 − ( c ′ ) 2 = 2 a 2 − c 2 + 2 a + 1 = a 2 + ( a + 1 ) 2 − c 2 = 0 . Therefore ( a ′ ) 2 + ( a ′ + 1 ) 2 = ( c ′ ) 2 , Q.E.D.
We know that 3 2 + 4 2 = 5 2 , so ( a , c ) = ( 3 , 5 ) is a valid starting point. It follows that ( a ′ , c ′ ) = ( 3 ⋅ 3 + 2 ⋅ 5 + 1 , 4 ⋅ 3 + 3 ⋅ 5 + 2 ) = ( 2 0 , 2 9 ) is another solution, as was given; next, ( a ′ ′ , c ′ ′ ) = ( 3 ⋅ 2 0 + 2 ⋅ 2 9 + 1 , 4 ⋅ 2 0 + 3 ⋅ 2 9 + 2 ) = ( 1 1 9 , 1 6 9 ) is a solution. Indeed, 1 6 9 is the answer to the problem.
Note 1: I have not proven that these are the only solutions... This method does not rule out the existence of ( 2 0 , 2 9 ) < ( a ⋆ , c ⋆ ) < ( 1 1 9 , 1 6 9 ) that satisfy the equation. Thus my solution is lacking; yet I post it here because it shows a nice elementary approach to this kind of problem.
Note 2: The question is, of course, how to get the recursion relation of the claim stated above. My inspiration was the repeated fraction approximation of 2 .
First, from a 2 + ( a + 1 ) 2 = c 2 2 ( a + 2 1 ) 2 = c 2 + 4 1 ( 2 a + 1 ) 2 = 2 c 2 + 2 1 we conclude 2 a + 1 ≈ 2 c . c 2 a + 1 ≈ 2 . Next, 2 = 1 + 2 + 2 + … 1 1 1 . Thus is one approximation of 2 = p / q , the next approximation is 1 + 1 + p / q 1 = 1 + p + q q = p + q p + 2 q , i.e. p ′ = p + 2 q and q ′ = p + q .
If q = c and p = 2 a + 1 , this becomes a ′ = a + c and c ′ = 2 a + c + 1 . Thus I tried ( a , c ) = ( 1 , 2 ) : p / q = 2 3 , a 2 + ( a + 1 ) 2 = 1 2 + 2 2 = 2 2 ; ( a ′ , c ′ ) = ( 3 , 5 ) : p / q = 5 7 , a 2 + ( a + 1 ) 2 = 3 2 + 4 2 = 5 2 ; ( a ′ ′ , c ′ ′ ) = ( 8 , 1 2 ) : p / q = 1 2 1 7 , a 2 + ( a + 1 ) 2 = 8 2 + 9 2 = 1 2 2 ; ( a ′ ′ ′ , c ′ ′ ′ ) = ( 2 0 , 2 9 ) : p / q = 2 9 4 9 , a 2 + ( a + 1 ) 2 = 2 0 2 + 2 1 2 = 2 9 2 . It appears that every other step results in a good equation, while in the other steps the LHS is one greater than the RHS. Thus I adjust my recursion formula by skipping a step: ( a ′ ′ , c ′ ′ ) = ( a ′ + c ′ , 2 a ′ + c ′ + 1 ) = ( 3 a + 2 c + 1 , 4 a + 3 c + 2 ) , and starting with the first valid pair ( a , c ) = ( 3 , 5 ) (or perhaps ( a , c ) = ( 0 , 1 ) ), I arrive at the claim above. The proof by induction is now straightforward.
Wow! This is superb. Continued fractions never cross my mind.
Problem Loading...
Note Loading...
Set Loading...
WLOG let b = a + 1 . a 2 + ( a + 1 ) 2 = 2 a 2 + 2 a + 1 = c 2 a = 4 − 2 ± 4 − 8 ( 1 − c 2 ) = 2 − 1 ± 2 c 2 − 1
For a to be an integer, we need 2 c 2 − 1 = n 2 for some integer n.
⇒ n 2 − 2 c 2 = − 1
This is a negative Pell's Equation which has fundamental solution ( n , c ) = ( 1 , 1 ) . Other solutions can be found by the recurrence relation n i + 1 = 3 n i + 4 c i and c i + 1 = 2 n i + 3 c i .
Hence the solutions are ( n , c ) = ( 1 , 1 ) , ( 7 , 5 ) , ( 4 1 , 2 9 ) , ( 2 3 9 , 1 6 9 )